Re-evaluation of a geothermal system model based on high-resolution gravity field inversion: A case study of the Maritaing geothermal field, Alor Regency, East Nusa Tenggara Province, Indonesia - Rholland A. Boling; Jehunias L. Tanesib; Hadi I. Sutaji; Laura A.S. Lapono; Richard Lewerissa (Kuwait Journal of Science)
The Maritaing region in East Nusa Tenggara Province, Indonesia, offers significant geothermal potential for direct power generation and use. This study aims to re-evaluate the geothermal system model in the Maritaing geothermal field using high-resolution gravity inversion. High-resolution gravimetric data were collected using satellite observations and data processing techniques, allowing a better understanding of the subsurface geological structure and density distribution of rocks associated with the geothermal reservoir. This study applied data corrections to acquire complete Bouguer anomalies, gravity gradient analysis to detect geological structures, and inversion modeling of residual gravity anomalies to predict subsurface rock density distribution. The complete Bouguer anomalies exhibit positive values ranging from 70 to 140 mGal and have a northwest–southeast orientation, indicating the existence of andesitic lava and pyroclastic volcanic rocks. Gravity gradient analysis determines the geological structures, such as faults or fractures, used as conduits to create Kura Hot Springs. The model provides useful insights into geological occurrences, such as faults, rock layers, and reservoir accumulations that support geothermal fluids. Based on the present study’s findings, we provide recommendations for developing and managing geothermal resources in the Maritaing area.